Kualitas Izin Pemakaian Tanah (IPT) Melalui Surabaya Single Window (SSW) Alfa di Sentra Pelayanan Publik (SPP) Menur Kota Surabaya - Wafa’, Naufal Syaraful; M, Meirinawati; Fanida, Eva Hany; Nourmanita, Neny Ayu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rise of information technology has prompted local governments to enhance public services using digital systems. In Surabaya, the website Surabaya Single Window (SSW) Alfa provides support for licensing services, including the Izin Pemakaian Tanah (IPT) at the Menur Public Service Center (SPP Menur). Nevertheless, the execution of IPT services through SSW Alfa encounters obstacles, including a lack of public knowledge regarding procedures, a requirement for assistance among older applicants, and sporadic technical difficulties. This research intends to assess the quality of IPT services offered digitally via SSW Alfa. A descriptive qualitative method was utilized, gathering data through observations, interviews, documentation, and a review of relevant literature. The quality of service was evaluated based on the indicators suggested by Sá et al. (2017). The results indicate that the quality of IPT services is generally satisfactory, especially in terms of transparency and adherence to procedures, despite ongoing issues with technology and access.